한국농업미생물자원센터(KACC)에 보존중인 Colletotrichum gloeosporioides와 C. acutatum의 재동정 - 김대호(Dae-Ho Kim); 전영아(Young-Ah Jeon); 고승주(Seung-Joo Go); 이종규(Jong-Kyu Lee); 홍승범(Seung-Beom Hong) (Sigmulbyeong yeon'gu, 2006)
Thirty-nine strains of Colletotrichum gloeosporioides and 5 strains of C. acutatum stored in Korean Agricultural Culture Collection(KACC) were re-identified based on molecular characteristics of ribosomal internal transcribed spacer(ITS) and partial $β$-tubulin gene and cultural characteristics on potato dextrose agar(PDA) and Benomyl-added PDA. As the results, 19 strains were identified as C. acutatum with 13 strains of group A2, 5 strains of group A3, and 1 strain of group A4. In addition, 20 strains were identified as C. gloeosporioides with 18 strains of ribosomal DNA group(RG) 4 and 2 strains of RG6. The rest were identified as C. boninense RG5(2 strains), C. coccodes RG2(2 strains), and C. dematium RG12(1 strain). Out of domestic 31 strains, 12 strains were identified as C. acutatum A2, one strain as C. acutatum A3, 14 strains as C. gloeosporioides RG4, 2 strains as C. gloeosporioides RG6, one strains as C. boninense RG5 and one strain as C. dematium RG12. We also discussed taxonomy of C. gloeosporioides and C. acutatum and composition of C. gloeosporioides/C. acutatum isolates from major crops in Korea. 한국농업미생물자원센터(Korean Agricultural Culture Collection, KACC)에 보존되어 있는 Colletotrichum gloeosporioides 39 균주와 C. acutatum 5 균주를 ribosomal DNA-ITS와 $β$-tubulin 부분염기서열과 PDA와 Benomyl-PDA배지에서의 생장 특성에 의하여 재동정 하였다. 그 결과 13 균주가 Talhinhas 등의 C. acutatum A2 그룹으로, 5 균주가 C. acutatum A3 그룹으로, 1 균주가 C. acutatum A4 그룹으로, 18 균주가 Moriwaki 등의 C. gloeosporioides ribosomal DNA group(RG) 4로 2 균주가 C. gioeosporioides RG6로 2 균주가 c. boninense RG5로 2 균주는 C. coccodes RG2 그리고 1 균주는 c. dematium RG12로 재동정되었다. 이들 중에서 한국에서 분리된 31 균주는 12 균주가 C. acutatum A2 그룹으로, 1 균주가 C. acutatum A3 그룹으로, 14 균주가 C. gloeosporioides RG4 로 2 균주가 C. gloeosporioides RG6로 1 균주가 C. boninense RG5로 그리고 1 균주는 C. dematium RG12로 동정되었다. 더불어 C. acutatum/C. gloeosporioides의 분류적인 특징과 국내 주요 기주별 분포 등에 대하여 고찰하였다.